Uso de tecnología aeroespacial para determinar el ciclo vegetativo del cultivo de maíz (Zea mays L.) a través de la respuesta espectral, considerando los tipos de semillas criollas y semillas híbridas - Torres Limones, Ángel Clemente (2022)
The research project was carried out at the Experimental Farm "La María", property of the Quevedo State Technical University. The Vegetative cycle of maize was evaluated through its spectral response in the types of seeds (Creole, Hybrid). Using field spectrometry and considering the physiological characteristics and the incidence of radiation levels in the different phases of development, taking into account the effect of radiometric parameters on these morphological changes as well as the physiological ones that occur as the culture continues. its development